Osseointegration of different implant surfaces in areas grafted with deproteinized bovine bone associated or not with fresh bone marrow—Preclinical study in rabbits - Leocádio, Amanda de Carvalho Silva [UNESP] (2021)
Objectives: To assess the influence of two different implant surfaces on osseointegration in maxillary sinuses of rabbits previously grafted with deproteinized bovine bone (DBB) associated or not with fresh bone marrow (BM). Material and methods: Sixteen New Zealand albino rabbits (males, 3.5/4.5 kg and 9–12 months old) were randomly divided into two groups with 8 rabbits each, according to the type of association of biomaterials used to fill the animals’ maxillary sinuses: DBB (Deproteinized Bovine Bone) and DBB/BM (Deproteinized bovine bone associated with fresh autologous bone marrow). Ninety (90) days following the grafting procedure, the animals received implants in the area with two different microstructures (SA-Sandblasting + acid attack and SA-H-Sandblasting + acid attack + immersion in 0.9% sodium chloride isotonic solution). All rabbits were euthanized 90 days after implant placement. The microtomographic analysis was performed to verify the number of mineralized tissues around the implants throughout their length (%BV/TV), while the histomorphometric analysis was performed to verify the percentage of bone-implant contact around the implants throughout their length (%BIC). Results: We observed no differences in the quantity for %BV/TV (DBB-SA:33.25 ± 19.67; DBB-SA-H:35.15 ± 22.17; DBB/BM-SA:39.71 ± 24.21; DBB/BM-SA-H:36.40 ± 23.07) and %BIC (DBB-SA:58.94 ± 24.37; DBB-SA-H:52.52 ± 24.36; DBB/BM-SA: 61.66 ± 14.60; DBB/BM-SA-H: 64.06 ± 23.30) between the groups assessed. Conclusions: The addition of BM and the type of surface did not influence the osseointegration of implants installed in areas grafted with sintered deproteinized bovine bone at high temperatures in the late period assessed.